(untitled) (Revista Brasileira Multidisciplinar, 2026)
Cassava has been cultivated for millennia, and cuttings are its main method of propagation. Although it can reproduce sexually, this characteristic is little studied, and understanding its reproductive biology is essential to assess the impacts of domestication. Thus, the objective of this study was to estimate the meiotic behavior and pollen grain viability of twenty local cassava varieties grown in the northern state of Mato Grosso, Brazil, in order to evaluate the reproductive potential of the different varieties. For this purpose, six months after planting, male flower buds in pre-anthesis and at different stages of development were collected from an experiment located in the municipality of Alta Floresta, Mato Grosso. In the preparation of the slides, 2% acetic orcein was used for meiotic analysis and triple Alexander reagent solution for pollen viability. The analyses were conducted at the Laboratory of Plant Genetics and Molecular Biology of Plants, Universidade do Estado de Mato Grosso. A total of 2,000 cells/pollen grains were counted per variety and the observations were made by the scanning method. The data were analyzed for normality using the Lilliefors test and, since they presented a normal distribution, were subjected to analysis of variance. The means were compared using the Scott-Knott test, at 5% probability. The analyses were performed using the Genes program. The varieties analyzed presented a high meiotic index (> 86%) and an average pollen viability rate (62%). The domestication of Manihot esculenta over generations has not compromised the reproductive potential of local varieties cultivated on the farms of family farmers in Mato Grosso. Farmers, in turn, play a crucial role as maintainers of this important genetic resource, contributing to the maintenance and conservation of cassava.